CONTEXT BASED ANALYSIS IN THE TRANSFORMATION OF RENDRA'S POETRY MUSICALIZATION - Muhammad Fikri; Tomi Arianto; Karmila Alam Syah Wellem; Khairunnisa Khairunnisa (IdeBahasa, 2023)
Poetry holds a very deep meaning that cannot even be only touched by a heuristic approach reading. When poetry is transformed into strings of tones or musicalization, the power of meaning in words will be even more stunning and make the affirmation of words stronger and more rooted. This article will reveal two of Rendra's transformation poems in the form of musicalized poems entitled “Serenada Kelabu” and “Kangen”. This article revealed the negation of "I" in poetry by using theoretical concepts textually and contextually. Textual analysis reveals the use of figurative language through the transformation of the poetry in the third song of Rendra's poem, while contextual analysis seeks to reveal the discourse built through the three poems. The method used in this research is a qualitative research method. The results of this study indicate that Both " Serenada Kelabu" and "Kangen" are poems in which the "I" that is opposed to the "You" and is defined by "love" is used to refer to the speaker. I feel so tormented as a result of my love for myself, tormented by my feelings of loss as well as loneliness. Because of love, "I" ceases to exist independently and is subjected to "you," whose existence only lives in the "I" as shadow.